Reliability and validity of the Chinese version of the Information Security Attitude Questionnaire for nurses - Wenguang Xie; Jingrui Li; Xiaoyu Liu; Yue Shu; Xinchen Yang; Yulu Deng; Chao Zhang (Wiley, 2024)
Abstract Aim Nurses play a crucial role within medical institutions, maintaining direct interaction with patient data. Despite this, there is a scarcity of tools for evaluating nurses' perspectives on patient information security. This study aimed to translate the Information Security Attitude Questionnaire into Chinese and validate its reliability and validity among clinical nurses. Design A cross‐sectional design. Methods A total of 728 clinical nurses from three hospitals in China participated in this study. The Information Security Attitude Questionnaire (ISA‐Q) was translated into Chinese utilizing the Brislin two‐way translation method. The reliability was assessed through internal consistency coefficient and test-retest reliability. The validity was determined through the Delphi expert consultation method and factor analysis. Results The Chinese version of ISA‐Q consists of 30 items. Cronbach's α coefficient of the questionnaire was 0.930, and Cronbach's α coefficient of the six dimensions ranged from 0.781 to 0.938. The split‐half reliability and test-retest reliability were 0.797 and 0.848, respectively. The content validity index (S‐CVI) was 0.962. Exploratory factor analysis revealed a 6‐factor structure supported by eigenvalues, total variance interpretation, and scree plots, accounting for a cumulative variance contribution rate of 69.436%. Confirmatory factor analysis further validated the 6‐factor structure, demonstrating an appropriate model fit. Conclusion The robust reliability and validity exhibited by the Chinese version of ISA‐Q establish it as a dependable tool for evaluating the information security attitudes of clinical nurses. Implications for Nursing Practice The Chinese iteration of the ISA‐Q questionnaire offers a profound insight into the information security attitudes held by clinical nurses. This understanding serves as a foundation for nursing managers to develop targeted intervention strategies aimed at fortifying nurses' information security attitudes, thereby enhancing patient safety.